Michael W. Burke-Gaffney and the UFO Debate in Atlantic Canada, 1947-1969 - Hayes, Matthew; Morritt, Noah (Scientia Canadensis, 2020)
This article offers a history of UFOs in postwar Atlantic Canada, as experienced by St. Mary’s University astronomer Michael W. Burke-Gaffney, an academic who engaged with UFOs and the interested public at a time when the standard response from his colleagues was to deny and debunk the phenomenon. The article argues that Burke-Gaffney’s efforts to explore UFOs with an open mind fit comfortably within Jennifer Hubbard’s framework of an “ideal of service.” However, by the end of his life and career, members of the public no longer admired Burke-Gaffney’s commitment to public education and service, coming to see him instead as yet another intellectual who aimed to ridicule and dismiss claims of UFO sightings as nothing other than misidentified natural phenomena. Burke-Gaffney’s work is important because it provides a means of tracking changes in the public’s perception of and deference to scientific authority and expertise in Atlantic Canada during the postwar period.